GENERAL ASPECTS OF PHOTOCHEMISTRY TO HUMAN - Mursyidi, Achmad (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
Photochemistry, the study of chemical reaction initiated by light plays an important role to human lifes. Photochemical reaction is intiated by the absorption of light giving excited molecules. The excited molecules, depending upon their structures and environment, may undergo various chemical reactions. Some very important and beneficial photochemical reactions occur in human body such as photochemical reaction of vision, the formation of vitamin D, and psoriasis medication. On the other hand, some photochemical reactions result in harmful effect to human, for examples, skin ageing, skin cancer, and cornea damage. Photosynthesis and photodegradation of pesticides are examples of photochemical reaction in the environment which are beneficial to human ienterset. In addition photochemical concept has been employed to synthesise drugs, nylon, and alkane-sulphates (detergents). However, some photochemical reactions create problem in the environment, i.e., formation of photochemical smogs, ozon layer depletion, and photodegaradion of drugs All those aspects of photochemistry are illustrated in this article.Key words: photochemistry, excited molecule, photodegradation, photooxidation, photosynthesis.